Body composition and bone health in long-term survivors of acute lymphoblastic leukaemia in childhood and adolescence: the protocol for a cross-sectional cohort study. Issue 1 (20th January 2015) - Barr, Ronald; Nayiager, Trishana; Gordon, Christopher; Marriott, Christopher; Athale, Uma
Abstract : Introduction: Success in the treatment of young people with cancer, as measured conventionally by survival rates, is mitigated by late effects of therapy that impose a burden of morbidity and limit life expectancy. Among these adverse sequelae are altered body composition, especially obesity, and compromised bone health in the form of osteoporosis and increased fragility. These outcomes are potentially reversible and even preventable. This study will examine measures of body composition and bone health in long-term survivors of acute lymphoblastic leukaemia (ALL) in childhood and adolescence. These measures will be complemented by measures of physical activity and health-related quality of life (HRQL). Methods and analysis: Survivors of ALL who are at least 10 years from diagnosis, following treatment on uniform protocols, will undergo measurements of body mass index; triceps skin fold thickness and mid-upper arm circumference; fat mass, lean body mass, skeletal muscle mass and bone mineral density by dual energy X-ray absorptiometry; trabecular and cortical bone indices and muscle density by peripheral quantitative CT; physical activity by the Habitual Activity Estimation Scale; and HRQL by Health Utilities Index instruments. Descriptive measures will be used for continuous variables and number (percent) for categorical variables. Associations between variables will be assessed using Fisher's exact t test and the χ 2 test; correlations will be tested by the Pearson correlation coefficient. Ethics and dissemination: The study is approved by the institutional research ethics board and is supported by a competitive funding award. Dissemination of the results will occur by presentations to scientific meetings and publications in peer-reviewed journals, and by posting summaries of the results on websites accessed by adolescent and young adult survivors of cancer.